Subjective ratings of masker disturbance during the perception of native and non-native speech - Kilman, Lisa; Zekveld, Adriana A.; Hällgren, Mathias; Rönnberg, Jerker (Frontiers in Psychology, 2015)
Abstract The aim of the present study was to address how 43 normal-hearing and hearing-impaired listeners subjectively experienced the disturbance generated by four masker conditions (i.e., stationary noise, fluctuating noise, Swedish two-talker babble and English two-talker babble) while listening to speech in two target languages (i.e., Swedish (native) or English (non-native). The participants were asked to evaluate their noise-disturbance experience on a continuous scale from 0 to 10 immediately after having performed each listening condition. The data demonstrated a three-way interaction effect between target language, masker condition, and group (hearing-impaired versus normal-hearing). The hearing-impaired listeners experienced the Swedish-babble masker as significantly more disturbing for the native target language (Swedish) than for the non-native language (English). Additionally, this masker was significantly more disturbing than each of the other masker types during the perception of Swedish target speech. The normal-hearing listeners, on the other hand, indicated that the Swedish speech-masker was more disturbing than the stationary and the fluctuating noise-maskers for the perception of English target speech. The NH listeners perceived more disturbance from the speech maskers than the noise maskers. The HI listeners did not perceive the speech maskers as generally more disturbing than the noise maskers. However, they had particular difficulty with the perception of native speech masked by native babble, a common condition in daily-life listening conditions. These results suggest that the characteristics of the different maskers applied in the current study seem to affect the perceived disturbance differently in hearing-impaired and normal-hearing listeners. There was no general difference in the perceived disturbance across conditions between the HI listeners and the NH listeners.